WhatsApp: - Arroz, Jorge Alexandre Harrison (2019)
BACKGROUND: WhatsApp (WA) is the most recent and attractive applicative among Smartphone users. The use of WA in healthcare environment has been shown of multiple benefices. Mozambique team involved in 2017 bed nets universal coverage campaign (UCC) implemented a distant mentoring strategy using WA. This study aims to perform a descriptive analysis of the use of WA as a supplementary tool for mentoring provincial and district health teams during bed nets universal coverage campaign in Mozambique. METHODS: Using WA, a qualitative study was carried out between March and July 2017. Seven WA groups were created. One group for central-level team, and six groups corresponding to each implementation province. The WA content was analyzed, grouped into separate themes, and subject to information triangulation among researchers and group participants. Saturation guided the quantity and quality of information. RESULTS: A total of 511 members were included in all WA groups. Of these, 96% were provincial WA groups. A total of 24,897 messages (text and images) were exchanged in all WA groups. The main communication form was text (22,660-91%), followed by images (2237-9%). Five themes emerged from content analyses: 1) administrative/financial, 2) logistic, 3) planning and implementation, 4) monitoring and evaluation, and 5) best practice. CONCLUSIONS: The use of WA during universal coverage bed nets campaign implementation in Mozambique fostered central-level coordination, providing implementation support to district and provincial teams, and promoting wider and timely information sharing among group members.